DEVELOPING THE STUDENTS’ COPYWRITING SKILLS THROUGH COPYWRITING PROJECT AT ENGLISH DEPARTMENT, FACULTY OF LANGUAGES AND LITERATURE, UNIVERSITAS NEGERI MAKASSAR - Andi Hajar; Lely Novia (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This research explores the implementation and outcomes of a copywriting project conducted for third-semester students of the Applied English (Business English Communication) Program, Diploma IV, English Department, Faculty of Languages and Literature, Universitas Negeri Makassar. Integrated into the compulsory Marketing and Advertising course, the project involved 60 students from two classes (A and B) during the 2025 academic year. This study aimed to analyze the quality of students' copywriting and identify the most preferred types of copywriting among them. Utilizing a qualitative research design with observational techniques, the project followed four main stages: product/service selection, buyer persona development, headline writing, and copywriting creation. Findings revealed gender-based trends in product/service choices. Male students tended to focus on automobiles, men’s fashion, perfumes, food and beverages, and service-based projects such as game top-ups, laptop repairs, plumbing, and travel. Female students predominantly selected cosmetics, women’s fashion, food and beverages, as well as services like laundry and tailoring. Students demonstrated awareness of target audiences by developing buyer personas and crafting headlines designed to attract attention. The final copywriting outputs showcased a variety of formats, with visual copy emerging as the most favored type. Overall, the project indicates that students showed interest and aptitude in copywriting. The activity is expected to enhance their practical skills and prepare them for future careers as copywriters in advertising agencies, digital media companies, or as freelancers.